Deli Serdang Regency Government Policy in Efforts to Prevent the Increase in the Incidence of Dengue Hemorrhagic Fever - Mery Christiyani; Nurmaini Nurmaini; Sri Malem Indirawati (Budapest International Research and Critics University, 2022)
The purpose of this study is to determine and analysis Deli Serdang Regency Government policy in efforts to prevent the increase in the incidence of dengue hemorrhagic fever from the relationship of rainfall and air temperature to the incidence of dengue hemorrhagic fever in Deli Serdang Regency. This type of research is ecological study research according to time. The object of this research is all climate data of Deli Serdang Regency recorded in the Meteorology, Climatology, and Geophysics Agency in 2016-2020 and data on the number of cases of dengue hemorrhagic fever in Deli Serdang Regency in 2016-2020. The method of data analysis in this study used bivariate analysis. The results show that rainfall has no correlation with the incidence of dengue hemorrhagic fever in Deli Serdang Regency. Air temperature has a moderate correlation with the incidence of dengue hemorrhagic fever in Deli Serdang Regency. Suggestions in this study are that Local Governments can take advantage of the results of this study in making policy in an effort to prevent increasing the incidence of dengue hemorrhagic fever in Deli Serdang Regency and be able to provide appropriate solutions in solving public health problems, especially the incidence of dengue hemorrhagic fever in Deli Serdang Regency.